2021
DOI: 10.1049/nbt2.12020
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone/gelatin electrospun nanofibres containing biologically produced tellurium nanoparticles as a potential wound dressing scaffold: Physicochemical, mechanical, and biological characterisation

Abstract: The biologically synthesised tellurium nanoparticles (Te NPs) were applied in the fabrication of Te NP-embedded polycaprolactone/gelatin (PCL/GEL) electrospun nanofibres and their antioxidant and in vivo wound healing properties were determined. The as-synthesised nanofibres were characterised using scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) spectroscopy and elemental mapping, thermogravimetric analysis (TGA), and Fourier-transform infrared (FTIR) spectroscopy. The mechanical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In addition, the stated scaffold had dose-dependent beneficial effects on collagen production and collagen horizontalization and decreased the edema and inflammation at the injury site. The results obtained strongly confirmed their healing activity, which can be useful for wound dressing …”
Section: Therapeutic Applications Of Nanofiberssupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, the stated scaffold had dose-dependent beneficial effects on collagen production and collagen horizontalization and decreased the edema and inflammation at the injury site. The results obtained strongly confirmed their healing activity, which can be useful for wound dressing …”
Section: Therapeutic Applications Of Nanofiberssupporting
confidence: 69%
“…Electrospun polymeric nanofibers have been viewed as promising materials for enhancing skin regeneration because of their structural resemblance to the extracellular matrix of healthy skin, ability to stimulate cell growth and proliferation, bacteriostatic activity, and suitability to deliver bioactive molecules to the wound site as shown in Figure . In a study conducted by Doostmohammadi et al, in vivo wound healing capabilities of tellurium nanoparticles embedded in polycaprolactone and gelatin nanofibers (electrospun) were investigated on wounds of Wistar rats using histopathology examination . Scaffolds containing nanoparticles showed the maximum healing with a score of 15 out of 19.…”
Section: Therapeutic Applications Of Nanofibersmentioning
confidence: 99%
“…The attachment of S. aureus and E. coli was decreased in the PGO-M2 nanofibers compared to the PGO nanofibers, which may be due to the negatively charged acrylic acid under a neutral pH, which repelled the negatively charged bacteria cells [ 73 ]. The dead bacteria cells were attached to the PGO-M2 surface due to the acidic property of M2, which triggered the bacteria attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, 10% w/v PCL was dissolved in chloroform: methanol (3:1 v/v ) solution and stirred for 24 h at room temperature [ 73 , 74 ]. Meanwhile, 10% w/w gelatin was dissolved in HFIP and stirred for 24 h. The PCL/gelatin (PG) solution was mixed at a 1:1 ( v/v ) solvent ratio and stirred for 24 h. Next, 1.0% ( w/v ) of GO, was added to the solution and stirred for another 24 h before electrospinning.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the antibacterial performance was also notably enhanced due to the encapsulation of Fe 3 O 4 nanoparticles. The existing studies also reported the design and development of electrospun ternary nanofiber mats with different multifunctional performances for wound dressing applications, such as ferric oxide/gelatin/glycerol nanofiber mats [ 116 ], copper oxide nanoparticle/gelatin/PCL nanofiber mats [ 117 ], cerium oxide nanoparticle/gelatin/PCL nanofiber mats [ 118 ], sliver nanoparticle/gelatin/PVA nanofiber mats [ 119 ], tellurium nanoparticle/gelatin/PCL nanofiber mats [ 120 ], and halloysite nanotube/gelatin/PCL nanofiber mats [ 121 ].…”
Section: Electrospun Gelatin-based Nanofibersmentioning
confidence: 99%